Reservoir Quality Evaluation: Unveiling Diagenetic Transformations through Mineralogical and Petrophysical Analyses of the Upper Miocene Lacustrine Sandstones in the Pannonian Basin System, Croatia (Rudarsko-geološko-naftni zbornik, 2024)
The Upper Miocene lacustrine sandstones of the North Croatian Basin, located in the southwestern Pannonian Basin System, represent significant reservoirs for hydrocarbon exploration, yet their diagenetic evolution remains poorly understood. This study offers a comprehensive investigation into the diagenesis of these sandstones, analyzing samples from 14 exploration wells in the Sava and Drava depressions. Using petrographic analyses, scanning electron microscopy with energy-dispersive X-ray spectroscopy (SEM-EDS), X-ray diffraction (XRD), and petrophysical measurements, we aimed to explain the diagenetic processes affecting reservoir quality and hydrocarbon productivity. Our results reveal a consistent grain size distribution, modal composition, and diagenetic alterations across both depressions. Compaction, evidenced by evolving grain contacts and pressure dissolution, leads to a depth-dependent reduction in porosity. Carbonate cements, notably calcite and Fe-dolomite/ankerite, are primary contributors to reduction of primary intergranular porosity, alongside clay minerals, quartz, feldspar, etc. Secondary porosity resulting from dissolution and redistribution processes also significantly influences overall porosity evolution. Clay minerals, detrital and authigenic, exhibit a complex interplay with other diagenetic processes, further reducing porosity and permeability. Authigenic clay minerals, including illite, chlorite, and kaolinite, act as pore-filling cement or coatings, hindering fluid flow. Paragenetic processes delineate the intricate relationship between mineralogical transformations and petrophysical properties, defining reservoir quality. Understanding diagenetic dynamics is essential for predicting reservoir quality, fluid migration pathways, and hydrocarbon productivity. This study fills a crucial knowledge gap regarding the diagenesis of the Upper Miocene lacustrine sandstones in the southwestern part of the Pannonian Basin System, providing insights vital for the energy sector and supporting sustainable resource development in the region.